Green Leasing Syariah: Inovasi Pembiayaan Berkelanjutan dalam Menghadapi Tantangan Ekonomi Global - Royyan As-Syafi'i; Mugiyati Mugiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze and formulate the concept of Sharia Green Leasing as a form of sustainable financing innovation that integrates the principles of the ijarah contract with the Environmental, Social, and Governance (ESG) framework. This study uses a qualitative approach with library research methods, as well as normative and conceptual analysis to examine the integration of sustainable finance theory, maqasid al-shari'ah, and Islamic financial innovation. Data were analyzed descriptively and exploratively and obtained from primary and secondary literature published between 2019 and 2025. The results indicate that Sharia Green Leasing has the potential to become a strategic financing instrument in supporting the green economy transition by financing environmentally friendly assets such as electric vehicles, energy-efficient engines, and low-carbon technologies. This study recommends strengthening regulations and developing operational guidelines by the Financial Services Authority (OJK) and the National Sharia Council-Indonesian Ulema Council (DSN-MUI), including the establishment of an independent verification mechanism to prevent greenwashing practices.